Chemical Profile of The Ethyl Acetate Extract of Aspergillus sydowi, 22-PLP1-F1, as Antibacterial Agent Against Clinically Resistant Strains of Staphylococcus aureus and Pseudomonas aeruginosa - Andi Setiawan; Fendi Setiawan; Susianti Susianti; Wawan Abdullah Setiawan; Peni Ahmadi; Riski Pangestu; John Hendri; Ni Luh Gede Ratna Juliasih (Pandawa Institute, 2025)
Mangrove endophytic fungi can produce bioactive substances with diverse biological functions. This study aims to evaluate the chemical profile of mangrove fungal endophytic extracts that inhibit clinical pathogenic bacteria resistant to various antibiotics. The fungi were collected from Petengoran mangrove forest, Lampung Province. Fungal isolates were grown on shrimp shell media using solid-state fermentation for 14 days. The fungal biomass was extracted using ethyl acetate, and the active components were evaluated using thin layer chromatography. The extract was partitioned with dichloromethane/water and its bioactivity was tested using TLC-bioautography and agar diffusion methods. The active fraction was identified using LC-MS/MS. The LC-MS/MS data was interpreted with SIRIUS 5.8.6, and the drug-likeness and toxicological characteristics were assessed using ADME/Tox and STopTox machine learning tools. Morphological analysis showed that isolate 22PLP1F1 was an Aspergillus sp., with spherical conidia at the hyphae tips. Through phylogenetic analysis it was confirmed that isolate 22PLP1F1 is Aspergillus sydowii with similarity 98.9%. Initial TLC examination indicated the production of alkaloids, polypeptides, and steroids. Antibacterial assays showed that the polar portion inhibited multi-drug resistance (MDR) Staphylococcus aureus, while the active fraction at 2 mg/mL inhibited MDR Pseudomonas aeruginosa. LC-MS/MS analysis revealed a major chromatogram peak at a retention time of 8.67; m/z 488.2196, suggesting a novel derivative of a compound at a retention time of 7.82; m/z 446.208. ADME/Tox analysis indicated that the compounds do not penetrate the BBB but remain in the GI absorption region. Further research is needed to elucidate the active compounds’ mechanism of action and conduct bioengineering studies.